Understanding Animate Agents - Wheatley, Thalia; Milleville, Shawn C.; Martin, Alex (Psychological Science, 2007)
How people understand the actions of animate agents has been vigorously debated. This debate has centered on two hypotheses focused on anatomically distinct neural substrates: The mirror-system hypothesis proposes that the understanding of others is achieved via action simulation, and the social-network hypothesis proposes that such understanding is achieved via the integration of critical biological properties (e.g., faces, affect). In this study, we assessed the areas of the brain that were engaged when people interpreted and imagined moving shapes as animate or inanimate. Although observing and imagining the moving shapes engaged the mirror system, only activation of the social network was modulated by animacy.